Management of metastatic colorectal cancer in patients ≥70 years - a single center experience - Huemer, Florian; Dunkl, Celine; Rinnerthaler, Gabriel; Schlick, Konstantin; Heregger, Ronald; Emmanuel, Klaus; Neureiter, Daniel; Klieser, Eckhard; Deutschmann, Michael; Roeder, Falk; Greil, Richard; Weiss, Lukas (Frontiers in Oncology, 2023)
Background: Age-standardized mortality rates for metastatic colorectal cancer (mCRC) are highest among elderly patients. In current clinical guidelines, treatment recommendations for this patient population are based on a limited number of clinical trials. Patients and Methods: In this monocentric, retrospective analysis we characterized patients aged ≥70 years undergoing systemic therapy for mCRC and overall survival (OS) was investigated. Results: We included 117 unselected, consecutive mCRC patients aged ≥70 years undergoing systemic therapy for mCRC between February 2009 and July 2022. Median OS was 25.6 months (95% CI: 21.8-29.4). The median age was 78 years (range: 70-90) and 21%, 48%, 26% and 5% had an ECOG performance score of 0, 1, 2, and 3, respectively. The median number of systemic therapy lines was 2 (range: 1-5). The choice of first-line chemotherapy backbone (doublet/triplet versus mono) did not impact OS (HR: 0.83, p=0.50) or the probability of receiving subsequent therapy (p=0.697). Metastasectomy and/or local ablative treatment in the liver, lung, peritoneum and/or other organs were applied in 26 patients (22%) with curative intent.First-line anti-EGFR-based therapy showed a trend towards longer OS compared to anti-VEGF-based therapy or chemotherapy alone in left-sided mCRC (anti-EGFR: 39.3 months versus anti-VEGF: 27.3 months versus chemotherapy alone: 13.8 months, p=0.105). In multivariable analysis, metastasectomy and/or local ablative treatment with curative intent (yes versus no, HR: 0.22, p<0.001), the ECOG performance score (2 versus 0, HR: 3.07, p=0.007; 3 versus 0, HR: 3.66, p=0.053) and the presence of liver metastases (yes versus no, HR: 1.79, p=0.049) were independently associated with OS. Conclusions: Our findings corroborate front-line monochemotherapy in combination with targeted therapy as the treatment of choice for elderly mCRC patients with palliative treatment intent. Metastasectomy and/or local ablative treatment with curative intent are feasible and may improve OS in selected elderly mCRC patients.